AB0452 SYSTEMATIC REVIEW OF GUIDELINES ON THE USE OF METHOTREXATE IN RHEUMATOID ARTHRITIS. (June 2019) - Guillen, Valeria Valerio; Hitchon, Carol; Loewen, Hal; Mody, Girish; Colmegna, Ines
Abstract : Background: Most guidelines on the use of methotrexate (MTX) in rheumatoid arthritis (RA) are issued by developed countries. MTX use in African 'least developed countries' (LDCs) requires considering costs of medical care, limited manpower and patients' beliefs. It is unknown whether current available MTX guidelines are relevant to LDCs. Objectives: To review existing guidelines/recommendations on the use of MTX for the treatment of RA prior to developing recommendations for LDCs. Methods: Electronic databases and guideline registries were searched for guidelines on MTX use in RA. Reviewers eliminated duplicates and selected the most updated guidelines. Similarities and discrepancies among recommendations are reported. Results: From 2111 citations, 23 full texts were screened and 13 included in the qualitative synthesis. Guidelines targeted rheumatologists (3/13) and other physicians involved in RA care (7/13). Half (6/13) of the guidelines comment on patient education. MTX is suggested as the first DMARD choice by 5/13 guidelines. Screening for risk factors associated with a higher risk of MTX toxicity (e.g. alcohol) is suggested in 4/13 guidelines. Eight guidelines discuss pre-MTX tests: all recommend baseline CBC, liver (mainly albumin and liver function tests), renal function tests (mainly serum creatinine) and HBV/HCV serologies. Seven recommend a baseline chest X-ray. Only 4/8 and 2/8 guidelines recommend HIV and TB screening respectively. Pneumococcus and influenza immunization are suggested by 3/13 guidelines that comment on vaccines, whereas HBV and HZV vaccines by 2/13. Pregnancy and lactation are stated as MTX contraindications by 5/13 guidelines; four recommend MTX discontinuation 3 months prior to conception in females. Only 2/13 guidelines comment on the need of contraception in patients of reproductive age on MTX. MTX starting dose is discussed by 7/13 guidelines: ≥10mg/wk (5/7); 12.5 -15 mg/week (1/7); and 6-8mg/week (1/7, guideline from Japan). The maximal dose of MTX recommended by 8/9 guidelines is 20-30mg/week. Dose escalation (2-5 mg) every 2-6 weeks is discussed by 4/9 guidelines. There is no uniformity on the initial administration route of MTX (3/6 oral, 3/6 either oral or parenteral). The use of higher MTX doses, increasing adherence, and inadequate clinical responses or intolerance are suggested indications for switching from oral to parenteral route (8/13). Folic acid supplementation is recommended by 8/13 guidelines; however specific dose and time intervals are not defined. CBC, liver and kidney monitoring are recommended for MTX treated patients by 8/13 guidelines. Specific laboratory investigations and monitoring intervals vary between guidelines. Eight guidelines agree that MTX could be continued throughout the perioperative period of elective orthopedic surgery. Three guidelines recommend MTX discontinuation in case of severe infection. MTX dose reduction is discussed by 3/13 guidelines, which recommend considering reduction with sustained remission (≥ 6 months). Conclusion: Existing guidelines do not uniformly address all aspects related to the MTX use in RA, and do not include a cost-effectiveness analysis. Adaptation of these guidelines for their implementation in LDCs is needed. Disclosure of Interests: Valeria Valerio Guillen: None declared, CArol Hitchon Grant/research support from: Pfizer, UCB (unrelated studies), Hal Loewen: None declared, Girish Mody: None declared, Ines Colmegna: None declared